Metastatic osteosarcoma: a challenging multidisciplinary treatment. Issue 5 (3rd May 2016) - Meazza, Cristina; Scanagatta, Paolo
ABSTRACT: Osteosarcoma is the most common malignant bone tumor, currently treated with pre-and postoperative chemotherapy in association with the surgical removal of the tumor. About 15–20% of patients have evidence of metastases at diagnosis, mostly in the lungs. Patients with metastatic disease still have a very poor prognosis, with approximately 20–30% of long-term survivors, as compared with 65–70% of patients with localized disease. The optimum management of these patients has not been standardized yet due to several patterns of metastatic disease harboring different prognosis. Complete surgical resection of all sites of disease is mandatory and predictive of survival. Patients with multiple sites of disease not amenable to complete surgery removal should be considered for innovative therapeutic approaches because of poor prognosis.